An Observational study of Skin Hydration with Its Risk Factors on Pruritus Severity Level in The Elderly at Sasana Tresna Werdha RIA Pembangunan Nursing Home, Ciracas, East Jakarta, Indonesia - Mashadi, Fladys Jashinta; Moniaga, Catharina Sagita (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The increasing elderly population increases the prevalence of health problems associated with the aging of the elderly. Aging causes the alteration of the skin function as a barrier in the elderly, which affects the skin hydration and can be influenced by various factors. Decreasing skin hydration causes dry skin. Dry skin can increase the risk and severity of pruritic skin, which is one of the most common skin problems in the elderly. Pruritus triggers the elders to scratch their skin and could result in opened wounds, which could lead to infection and a lower quality of life. To get a description of the skin hydration along with its risk factors’ data distribution (such as age, total daily liquid consumption, daily moisturizer usage frequency, and hot water usage for bathing) on the elders with and without pruritus, as well as on each of the pruritus severity levels of the elders at Sasana Tresna Werdha RIA Pembangunan Nursing Home.  This research used an observational-descriptive approach using a cross-sectional method. In total, there are 41 elders at Sasana Tresna Werdha RIA Pembangunan Nursing Home who participated in this research. The sampling technique used was total sampling. The data were collected through interviews using 12-items pruritus severity scale questionnaires and measurements with Large LCD BIA Skin Analyzer for skin hydration values. The data were analyzed using a univariate analysis. Crosstabs will be made between variables to be observed in more detail about the possibilities of interrelationships between the variables. From the 41 elders at Sasana Tresna Werdha RIA Pembangunan Nursing Home, there were 16 elders (39%) without pruritus and 25 elders (61%) with pruritus, which composed of 6 elders (24%) with mild pruritus, 15 elders (60%) with moderate pruritus, and 4 elders (16%) with severe pruritus. The mean of skin hydration of the elders without pruritus was 52.7% and with pruritus was 44.5%. Among the elders with pruritus, the mean of skin hydration of them with mild pruritus was 48%, moderate pruritus was 45.5%, and severe pruritus was 35.6%. This data showed that the population of elders with pruritus was increasing along with an increase in age. Our data also showed that the majority of the elders had a total daily liquid consumption of less than eight glasses and it was increasing along with an increase in pruritus severity level. Further, the data showed that the majority of elders with pruritus never used daily moisturizer and always used hot water for daily bathing. The mean of skin hydration of the elders without pruritus was 52.7% and that of the elders with pruritus was 44.5%. The lowering of the skin hydration level was in parallel with the increase of the pruritus severity of the elders. There was an increase in the population of the elders with pruritus along with an increase in age. The percentage of elders with a total daily liquid consumption of less than eight glasses was increasing along with an increase in pruritus severity levels. The majority of the elders with pruritus never used daily moisturizer and always used hot water for daily bathing. Keywords: Skin Hydration, Pruritus Severity Level, Elderly, Age, Liquid Consumption, Moisturizer Usage, Hot Water